Mood Disorder in Adolescents with Diabetes Mellitus in Kirkuk City (Medico Legal Update, 2020)
Objective: Assess the severity of mood disorders in adolescents with type 1 diabetes mellitus (TIDM), andidentify the relationship between the mood disorder and some socio-demographic characteristics amongAdolescents.Methodology: A descriptive study was carried out at center of diabetics & endocrine disease in the Kirkukcity, from February, 10th, 2019 up to November 10th, 2019 in order to achieve the objectives of the presentstudy. Non-Probability (Purposive) sample of (70) patients. Developed questionnaire was constructed for thepurpose of the study which consisted of two parts: the demographic characteristics; and Child DepressionInventory (CDI) it is a Likert-type scale consisting of 27 items . The data were collected through the use ofinterview technique (face to face). The data was analyzed through the application of descriptive statisticalanalysis (Frequency, Percentage (%), Mean of Score) and inferential statistic (ANOVA & t. test).Results: The findings of the study indicated that the majority of the sample (40%) of them with age group(16-17 years), (54%) of them were male, (71%) of them single, the most of the sample were graduated fromintermediate school (47%), regarding to the occupation (42.9%) of the sample was student, and in relationto financial status the majority of the adolescent was in barely sufficient and constitute (77%).